Synthesis, crystal structures and dynamic NMR studies of novel trinuclear copper(I) halide complexes with 2,5-bis[(diphenylphosphino)-methyl]thiophene - Chen, B.-L. (2014)
Journal of the Chemical Society - Dalton Transactions